ABOUT FEATURES OF SIMULATION MODULE IN SOLIDWORKS - Cătălin IANCU (Fiabilitate şi Durabilitate)
In this paper are presented the additional features and analysis steps of Simulation module in SolidWorks, for conducting a more detailed study of designed parts. There are presented the module features, the settings that have to be done for such analysis and the results shown after analysis.